Examining Predictors of Teacher Performance: Leadership, Motivation, and Work Climate in Faith-Based Education - Nancy Nayoan; Slamet Lestari (Papanda Publisher, 2026)
Teacher performance is a critical determinant of educational quality, yet the mechanisms through which school leadership, teacher motivation, and work climate influence performance in faith-based institutions remain underexplored. This quantitative cross-sectional study examined 87 teachers from Adventist Junior High Schools in Manado City, Indonesia, using validated questionnaires measuring leadership, motivation, work climate, and teacher performance. Data were analyzed using multiple linear regression with SPSS 25.0. The overall model was highly significant (F = 99.96, p < 0.001, Adjusted R² = 0.775), explaining 77.5% of performance variance. Teacher motivation emerged as the strongest predictor (β = 0.788, p < 0.001), followed by work climate (β = 0.372, p < 0.001). Unexpectedly, school principal leadership showed no significant effect (β = -0.158, p = 0.121). Findings extend Self-Determination Theory into faith-based educational contexts, demonstrating that autonomous motivation and supportive organizational environments supersede direct leadership influences in predicting teacher performance. The non-significant leadership effect challenges traditional hierarchical models and suggests indirect pathways through motivational and climate variables. Educational administrators should prioritize interventions enhancing intrinsic motivation and cultivating positive work climates. Future research should employ longitudinal designs examining mediating mechanisms and expand sampling to diverse educational contexts.